ISLANDS OF FREEDOM: LIBRARY OF CONGRESS, WIKILEAKS, AND THE ARCHIVE IMAGINARY - Witte, John James (AoIR Selected Papers of Internet Research, 2015)
On December 3, 2010, the Library of Congress confirmed on its blog that it had blocked Wikileaks from all of its internal servers, banning the site across the entirety of its computer systems and disallowing access to the site and its archives within the walls of the LC’s main reading rooms. The decision to block the website was made in the wake of a series of releases from Wikileaks, including more than 250,000 classified State Department cablesand the additional release of 6,500 quasi-secret reports produced by the Congressional Research Service, a subbranch of the LC meant to serve the needs of the United States Congress. It’s the peculiarly ineffective means of censorship that they chose that interests me most. Patrons of the library need only to pull out their smart phones to gain access to Wikileaks documents within the walls of the Jefferson reading room. Federal employees can access the documents from home, and, even if it were effective, the ban would only succeed in guaranteeing that those working for the LC and other branches of the federal government are less informed than members of the general public. So why did the library ban Wikileaks? I believe the answer to these questions has to do with competing definitions of the public-ness, a concern which is shared by both Wikileaks and the Library of Congress to negotiate the competing ideological demands of both archive and nation, two metaphorical imaginaries with overlapping but divergent ideologies.